Analysis of the ageing effect on the cyclic tension–compression loading behaviour of bitumen and mastics. (20th May 2020) - Micaelo, R.; Botella, R.; Pérez-Jiménez, F.; Sá da Costa, M.
Highlights: Mineral fillers may induce a greater stiffening effect than ageing treatment; The stiffening effect of filler and ageing increases with the temperature; The stiffness increase with ageing may vary with the loading mode used for testing; EBADE test did not show that the mastics are less affected by ageing than the bitumen. Abstract: Within the bituminous mixture the binder is subjected to different stress-state modes but the cyclic loading response is usually characterized on shear mode. This research investigates the evolution with ageing of the undamaged linear rheological behaviour and resistance to cyclic loading of bituminous materials using a tension–compression strain-sweep test. The results show that, similarly to the shear mode response, mineral fillers may induce a greater stiffening effect than ageing treatment, although the comparative evolution with ageing of materials may differ from that based on the shear mode response. The damage progression rate increases faster at lower temperatures and for the stiffer materials (mastics), where the flow deformation contribution to crack formation is smaller. The testing temperature is determinant for the evaluation of the effect of ageing and filler on fatigue resistance.